Aqueous extract from Opuntia megapotamica fruit pulp promotes osteoblast activity - Valeria Gili; Juan A Laiuppa; Graciela E Santillán (International Journal of Spine Research - Peertechz Publications, 2020)
Objetive: Osteoporosis and osteopenia are age-related chronic diseases with increased morbidity rates among postmenopausal women. Natural products investigation for prevention and treatment of these conditions is growing, due, in part, to the fact that they allow longer exposure times and minor secondary complications than synthetic drugs. Opuntia plants (Cactaceae) have been shown to possess a broad spectrum of medicinal properties. Opuntia megapotamica is an autochthonous species from Argentina but its action on bone metabolism has not yet been studied. The work aims is to evaluate the action of aqueous extracts of O. megapotamica fruits on the activity and function of osteoblasts in vitrO. Methods: Primary osteoblasts were obtained by digestion of the cranial bones of 3-5 day-old Wistar rats. Cells were treated with different dilutions of the aqueous extract (1/50-1/1000), then viability, proliferation, differentiation and mineralization were assessed at the corresponding time points. Results: Dilution of extract 1/100 induced a slight but significant increase in cell viability with respect to control (p< 0.05) whereas the other conditions showed no changes. In addition, dilutions of extract 1/100 and 1/1000 significantly increased cell proliferation at 24 and 48 h with respect to the control (p< 0.05). Culture mineralization, showed a rising trend with respect to the control at 15 days of treatment with 1/1000 extract dilution. Conclusions: The results show that the aqueous extract of O. megapotamica fruit increases the number and improves the biological functions of osteoblasts, suggesting its potential use as an alternative treatment for postmenopausal bone deficit.